Uganda: A new set of utility consistent poverty lines - Bjorn Van Campenhout; Haruna Sekabira; Fiona Nattembo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Uganda has seen impressive economic growth and substantial poverty reductions over the past few decades. Today, official headcount poverty stands at about 20 per cent. However, recent research relying on non-monetary wealth indicators challenges official poverty statistics and suggests that headcount poverty is about 60 per cent higher. We argue that an outdated poverty line that does not take into consideration the spatial variation of diets in Uganda could explain the divergence. In this paper, we document how we estimate a new set of utility consistent poverty lines for Uganda using the Uganda National Household Survey of 2012-13 and use these updated poverty lines to calculate poverty. We find poverty levels to be higher and much more in line with what other studies suggest.
Keywords: I32; O55; O21; 330; poverty lines; diet; basic needs; spatial patterns; Uganda